Filosofia Lean: modelo para implantação no centro cirúrgico de hospital privado do Rio Grande do Norte - Oliveira Neto, Antonio Moliterno de (2018)
The lean philosophy, born in the automotive industry in the 1940s, has been gaining ground in other areas, such as goods and services. Its initial application in the health sector can be seen from 2002, but not much is said about its specific implementation for the surgical center. Given this gap, this study proposes a model for implementing lean philosophy in the surgical center of a private hospital in Rio Grande do Norte. The study is characterized as explanatory, using qualitative and quantitative methods. As regards the planning of the research, it was opted for bibliographic research, case study and action research. The developed study aimed to analyze the organizational environment of a surgical center in a private hospital in Rio Grande do Norte. For this purpose, the current scenario of the structure and processes of the sector was evaluated and then mapped in order to generate value for the customer, as well as to eliminate waste. As result, this study employs lean service design methodologies and tools for a better understanding, systematization and improvement of the surgical center activities, from the point of view of consumer, reducing lead time. This is achieved by the reconfiguration of the processes, in order to bring improvement in the flow of the patients, removing the activities that do not add value to the process. The lean model helped solving these problems. This study shows that, even in its first steps, lean philosophy can be very powerful in the health services secto